2005
DOI: 10.1007/s10517-005-0500-2
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal Variations in Qualitative Composition of Breast Milk in Women with Iron Deficiency

Abstract: Biorhythms of iron metabolism in healthy women and patients with iron deficiency were studied during lactation. Healthy nursing women were characterized by circadian variations in the concentrations of iron, alpha-tocopherol, and malonic dialdehyde in breast milk. Diurnal variations in iron concentration, antioxidant potential, and lipid peroxidation in breast milk depended on iron metabolism in nursing women. Iron deficiency was accompanied by a decrease in the concentrations of alpha-tocopherol and iron, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 5 publications
1
14
0
1
Order By: Relevance
“…Overall, vitamins A, B1 (thiamine), B2 (riboflavin), B3 (niacin), B6 (pyridoxine), B8 (biotin), B12 (cobalamin), vitamin E (tocopherol), and choline do not demonstrate circadian variation [ 27 , 33 , 63 , 65 , 66 , 67 , 68 ], whereas vitamin B11 (folate) shows circadian variation in one study [ 69 ]. However, the evidence is limited and, therefore, results on the presence of circadian variation in human milk vitamins are inconclusive.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, vitamins A, B1 (thiamine), B2 (riboflavin), B3 (niacin), B6 (pyridoxine), B8 (biotin), B12 (cobalamin), vitamin E (tocopherol), and choline do not demonstrate circadian variation [ 27 , 33 , 63 , 65 , 66 , 67 , 68 ], whereas vitamin B11 (folate) shows circadian variation in one study [ 69 ]. However, the evidence is limited and, therefore, results on the presence of circadian variation in human milk vitamins are inconclusive.…”
Section: Resultsmentioning
confidence: 99%
“…food consumption pattern) or socioeconomic status, factors which might affect micronutrient levels in breast milk. Furthermore, many substances such as vitamins and minerals in breast milk are known to have diurnal variation [ 47 48 49 ], which makes the time of day for milk collection important. In this study, the specific time of day at which breast milk was expressed and collected was not standardized.…”
Section: Discussionmentioning
confidence: 99%
“…67 Studies have shown diurnal variation in calcium, phosphorus, magnesium, iron, nucleotides, cortisol, and melatonin. [68][69][70][71][72][73][74][75] Other factors affecting breast milk…”
Section: Composition Of Expressed Fresh Human Milkmentioning
confidence: 99%